2011
DOI: 10.1007/s11096-010-9467-9
|View full text |Cite
|
Sign up to set email alerts
|

Coronary heart disease: health knowledge and behaviour

Abstract: The deficit in CHD knowledge could translate into inadequate preventative behaviour patterns and suboptimal clinical outcomes. If community pharmacists wish to become increasingly involved in public health delivery relating to CHD they need to develop effective and accessible services and promote these to the public who at present do not recognise this role of the community pharmacist.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

28
44
10
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 40 publications
(83 citation statements)
references
References 22 publications
28
44
10
1
Order By: Relevance
“…Our results indicated no association between self reported level of health and the knowledge and awareness, which is consistent with other studies [19,23]. Our findings showed no association between personal income and the knowledge and awareness.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Our results indicated no association between self reported level of health and the knowledge and awareness, which is consistent with other studies [19,23]. Our findings showed no association between personal income and the knowledge and awareness.…”
Section: Discussionsupporting
confidence: 92%
“…This is not in line with findings of Saeed et al (2009) in India and Al Hamarneh et al (2011) in North Ireland. Both studies indicated that practicing exercise is associated with knowledge on CVDs.…”
Section: Discussioncontrasting
confidence: 91%
See 3 more Smart Citations